Can we change mathematics test items to be more equitable to ELLs? (Part 1 of 3) - Norval, Brooke (Ohio Journal of School Mathematics, 2019)
Throughout the next three issues of the Ohio Journal of School Mathematics, we will be including one article in each issue about English language learners (ELLs) and how to modify mathematics test items to make them more equitable for ELLs. In this first installment, the author summarizes data indicating that ELL students score significantly lower on National Assessment for Educational Progress (NAEP) mathematics items than non-ELL students. Moreover, the author provides a review of literature supporting language modification of mathematics test items.